Exploring untapped bacterial communities and potential polypropylene-degrading enzymes from mangrove sediment through metagenomics analysis - Pawano, Onnipa; Jenpuntarat, Nuttarin; Streit, Wolfgang R.; Pérez-García, Pablo; Pongtharangkul, Thunyarat; Phinyocheep, Pranee; Thayanukul, Parinda; Euanorasetr, Jirayut; Intra, Bungonsiri (Frontiers in Microbiology, 2024)
The versatility of plastic has resulted in huge amounts being consumed annually. Mismanagement of post-consumption plastic material has led to plastic waste pollution. Biodegradation of plastic by microorganisms has emerged as a potential solution to this problem. Therefore, this study aimed to investigate the microbial communities involved in the biodegradation of polypropylene (PP). Mangrove soil was enriched with virgin PP sheets or chemically pretreated PP comparing between two and four months enrichment to promote the growth of bacteria involved in PP biodegradation. The diversity of the resulting microbial communities was accessed through 16S metagenomic sequencing. The results indicated that Xanthomonadaceae, unclassified Gaiellales, and Nocardioidaceae were promoted during the enrichment. Additionally, shotgun metagenomics was used to investigate enzymes involved in plastic biodegradation. The results revealed the presence of various putative plastic-degrading enzymes in the mangrove soil, including alcohol dehydrogenase, aldehyde dehydrogenase, and alkane hydroxylase. The degradation of PP plastic was determined using Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR-FTIR), Scanning Electron Microscopy (SEM), and Water Contact Angle measurements. The FTIR spectra showed a reduced peak intensity of enriched and pretreated PP compared to the control. SEM images revealed the presence of bacterial biofilms as well as cracks on the PP surface. Corresponding to the FTIR and SEM analysis, the water contact angle measurement indicated a decrease in the hydrophobicity of PP and pretreated PP surface during the enrichment.